The effects of participation in the activities of the supplemental teaching guide for physical fitness on the performance of 11-15 year old Iloilo boys and girls in the ICSPFT physical performance battery - Provido, Leticia G. 1937-
This study determined the effect of the participation of 12 to 15 year old Iloilo boys and girls in the activities of the Supplemental Teaching Guide for Physical Fitness for eight weeks in terms of their speed, leg power, strength and endurance, agility, abdominal strength and endurance, flexibility, and cardiovascular endurance.
Thesis (M.A.T.Physical Education)--University of the Philippines.
Keywords: Physical fitness; Physical education and training